Morphological Analysis and Biochemical Properties of Staphylococcus aureus Cultures Grown on Alternative Media Peanut Flour (Arachis Hypogaea L.) - Yudha Anggit Jiwantoro; Salmania Putri (Poltekkes Kemenkes Mataram, 2023)
Sources of nutrition especially sufficient protein, is needed for the growth of Staphylococcus aureus bacteria. Synthetic media is the most common medium for growing Staphylococcus aureus. Peanut is a biological source in nature with a higher protein content than synthetic materials which can be used as an alternative. Objective to determine the morphology and biochemical properties of Staphylococcus aureus bacteria grown on alternative media of peanut flour (Arachis hypogaea L.) as a medium for bacterial growth. This is a True-Experiment study with a completely randomized design. The experimental unit consists of five variations in the concentration of peanut alternative media. The sampling technique was done by simple random sampling. Data analysis used Descriptive. Staphylococcus aureus bacteria can grow at all concentrations of alternative media of peanut flour. The colony size at concentration of 2% was very small with weakly fermented mannitol. Meanwhile a concentration of 3% to 5% produces moderately fermented mannitol. The concentration of 6% is the concentration with the most widely fermented mannitol. The biochemical tests of all concentrations yielded positive catalase and coagulase, and the sugar test yielded positive reactions. An alternative medium of peanut flour can be used as a medium for the growth of Staphylococcus aureus bacteria with the most effective concentration of 6%.